(untitled) (Contexto (Universidad de los Llanos), 2024)
The Universidad de los Llanos works continuously to improve the quality of education and the experiences of the student community, for which it generates scenarios and events that allow achieving this goal. In this regard, a training cycle was recently held on ’Analysis of Public Policies and Formulation and Evaluation of Research Projects, an initiative led by the Faculty of Economic Sciences aimed at teachers, research groups and students.